IMPLEMENTATION OF DIFFERENTIATED LEARNING IN PANCASILA CITIZENSHIP EDUCATION IN THE INDEPENDENT CURRICULUM IN PRIMARY SCHOOL - Nur Laili; Nadlir (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2024)
Abstract Differentiated learning is a learning strategy focusing on students' individual learning needs. The purpose of this study was to reveal the process of implementing differentiated learning in PPKn learning in grade V. This field research was conducted at SDN Petemon Surabaya using a qualitative method with a descriptive approach. The subjects of this study consisted of PPKn teachers and 30 grade V students. The study results showed that applying differentiated learning in Pancasila citizenship education helped students better understand and internalize PPKn values​​, improved learning quality, and increased students' interest in learning. Teachers implemented problem-based learning, problem-solving skills learning, creative and fun learning, group-based learning, and character-based learning. Differentiated PPKn learning at SDN Petemon provides learning opportunities to ensure appropriateness in learning in the form of materials tailored to students' interests and backgrounds, allowing for a better understanding of Pancasila values and varied teaching strategies. Students are free to choose how they show their understanding to increase engagement and self-confidence.